19 Experimental study on postoperative adhesions between tendon and different tissues. (5th December 2017) - Su, Y; Wang, WM; Meng, XJ; Gu, GS; Yu, MY; Yan, ZF; Ma, YM; Dong, XL; Sun, Q; Zhao, DW
Abstract : Objectives: The aim of this paper is to observe the gross and histological changes of postoperative adhesions between tendon and different tissues in the same environment in animal models. Methods: Models of flexor tendon rupture and superficial tendon sheath defect were made in chickens, and then the tendons were sutured. Two and four weeks after the operation toe specimens of the surgical site were sampled. By gross and histological observation, adhesion between the tendon and the subcutaneous tissue, and adhesion between the tendon and the remnant tendon sheath were observed, respectively. Fisher exact test was used to analyse the gross observation results. Results: Gross observation: with time, tissue proliferation surrounding the tendon increased. The tissue proliferation between the tendon and the subcutaneous tissue was more than that between the tendon and the remnant tendon sheath. Fisher exact test showed the adhesion between the tendon and the remnant tendon sheath was significantly different from the adhesion between the tendon and the subcutaneous tissue. Histological observation: with time, fibrous connective tissue increased around the tendon, which was more pronounced between the tendon and the subcutaneous tissue than between the tendon and the remnant tendon sheath. Conclusion: Postoperative adhesions between the tendon and different tissues differ. More tissue adhesion formed between the tendon and the subcutaneous tissue than between the tendon and the remnant sheath.